Analisis Manajemen Risiko Teknologi Informasi Software PEGA Menggunakan ISO 31000 - Joshua Ecleas; Augie David Manuputty (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
PEGA is a software that is used by PT. Asuransi Sinar Mas to support the service and and productivitsy of the company. PEGA has a number of uses, such as to record employee’s absence, check the productivy of the employees, add new insurance policy, and read said policy. PEGA is influencial to support the business processes of PT. Asuransi Sinar Mas, an insurance company. While running said business processes, there is a lot of risk that threatens the flow of business the company has. Thus a risk management analysis is needed to lessen the chance of said risk to occur, so the company’s business flow remains uninterrupted. The ISO 31000 risk management guidelines can be used to analyze those risk. Then, a risk assessment and treatment is needed to identify the risk and the solution to such risk. The results of this study can be useful and serve as suggestions for company to minimize or eliminate risks that can hinder the smooth running of the business of PT. Sinar Mas Insurance.